Composition of Waste From Seagoing Ships - Kári-Horváth, Attila; Lantos, Zsolt; Sztancsek, Ákos; Kristóf, Gábor (Journal of Central European Green Innovation, 2024)
In shipping, great attention is paid to reducing environmental impacts. This is all the more justified as the most common marine fuel today is heavy fuel oil, which contains 3,500 times more sulphur than conventional diesel fuel. Accordingly, there are now floating hotels in worldwide that use LNG as a green fuel. In this article, we will try to gather literature strongly related to this topic to develop a detailed technology for disposing of these wastes in a later work.
Keywords: ship-generated waste; waste recovery; MARPOL convention; sewage; disposal